Rancang Bangun Sistem Pemantau Ketersediaan Sabun dan Tisu pada Toilet Bandara Berbasis IoT - Lestariningsih, Dwi Wahyu; Djajadi, Arko; Adhistian, Patria; Wibowo, Priyo (Politeknik Penerbangan Indonesia Curug, 2024)
Public toilets, especially at airports, play an important role in ensuring the comfort and cleanliness of traveling passengers. The unavailability of tissue and soap in toilets is often a problem at airports. This research aims to develop a soap and tissue monitoring system in airport toilets based on the Internet of Things (IoT) using Narrowband IoT (NB-IoT) technology and the Thingsboard platform. The prototype system for monitoring the availability of airport soap and toilet tissue was successfully created using an Arduino Nano, SIM7000C and was able to communicate with the Thingsboard via the MQTT protocol, making it possible to monitor the availability of sanitation facilities in real-time. The measurement results show that the device can operate well using an IMR 18650 battery for up to 27 hours. This system is able to provide information on the level of contents of soap containers and the capacity of available tissue along with its location. This research underlines the potential of IoT technology in overcoming the problem of unavailability of soap and tissue, aimed at increasing user comfort and maintaining the cleanliness of public facilities at airports.